Estudo eletrofisiológico da audição em crianças verticalmente infectadas pelo vírus da imunodeficiência humana em uso de terapia antirretroviral - Vanessa Ferreira Mariz (2009)
Introduction: Many studies are found indicating increased risk of hearingimpairment in pediatric HIV infection, seen in abnormalities found in the auditory brainstem response (ABR) that suggests conductive and neural commitment. Objective: Describe the electrophysiological responses of auditory brainstem in a group of children infected with HIV-I in the Hospital of the Federal University of Minas Gerais and compare the results to a group of children without infection, the same track age and sociocultural factors, from public school in the city of Belo Horizonte Methodology:.All patients in both groups were submitted toelectrophysiological assessment of hearing by ABR MASBE equipment by Contronic®. The transversal comparative study was approved by the Ethics Committee of the institution and carried out from December 2007 to December 2008 Results: Both groups,the study and control, were composed of 36 individuals, 52.8% and 47.2% females respectively. The average age in the group infected was 10.41 (SD = 1.81) and 9.11 (SD = 1.30) in group without infection. All the infected children were in regular use of highly active antiretroviral therapy(Highly Active Antiretroviral Therapy, HAART).The ABR analysis did not observed statistical significance between groups for absolute latencies of waves I, III and V, the interpeak intervals I-III, IV and V and the interaural difference ofwave V. Three results suggestive of condutive impairment were found in the study group.No results were suggestive of central auditory impairment. Most of these patients had a previous history of earache, but not at the time of evaluation. Despite the non significant differences, infected patients with abnormal ABR, had a trend to higher clinical staging of the disease (B3 , C1, C2). Conclusion: The electrophysiological responses of ABR in HIV-infected children, aged between 7 and 13 years, in use of HAART and controlled clinical, immunological and virological were not significant from the responses of children without infection. However, children infected by HIV-I and with abnormal ABR showed conductive impairment and trends to a higher clinical staging of the disease. The results indicates that the ABR was enough to assess the peripheral and central hearing however, suggests the need for implementing new auditory electrophysiological studies of middle and long latency broader.Children infected with HIV-I mustundergo early audiological assessment followed by regular monitoring to detect changes and to define intervention strategies.